Effectiveness of a psycho-educational intervention for people with suicidal conduct in the prison environment, N’viu project: a randomized control trial - Foguet-Boreu, Quintí; Capdevila-Capdevila, Manel; Riesco- Miranda, Lola; Torres, Ana Sanjuan; Framis-Ferrer, Berta; Pons-Baños, Judit; Muñoz, Saray Valdivieso (International Journal of Clinical Trials, 2022)
Background: Suicide rates are higher in the prison environment than in the general population. Prevention involves strategies to promote mental health, early diagnosis, treatment and identification of precipitating factors. The aim of this study is to evaluate the effectiveness of a psychoeducational group intervention performed by rehabilitation professionals to decrease the number of suicidal behaviors in the penitentiary environment. Methods: This study has been designed as a multicentric, randomized, two parallel-group, controlled trial. The study population will be male and female inmates of nine prisons of Catalonia (Spain). The primary outcome will be the total number of suicidal behaviours for 12 months of follow-up. Secondary outcomes will be suicide risk evaluated with the international neuropsychiatric interview (MINI); the severity of suicidal ideations assessed with the Columbia-suicide severity rating scale (C-SSRS), the presence of depressive and anxiety symptoms [Hamilton depression rating scale (HDRS) and Hamilton anxiety rating scale (HARS)] and health-related quality of life (EQ-5D). Other variables will be clinical and socio-demographic. Intervention will consist of 17 psychoeducation sessions for the intervention group and information on suicide for the control group. Conclusions: This project aims to assess the effectiveness of a psycho-educational intervention on reducing the number of suicidal behaviours in the prison environment. If positive, the prison community will have a new tool to curb suicide in prisons. Trial registration: The trial was registered on clinicalTrials.gov on 19 January 2022 (NCT05195554).